A New Tool for Faster Construction of Marine Biotechnology Collaborative Networks - Rotter, Ana (2021)
COST Action CA18238 (Ocean4Biotech) P1-0245 P1-0237 Project No. 7032, internal ref. 8MED20_4.1_SP_001 (EMFF) 2014-2020 PDOC/19/02/01